Fulminant Japanese Spotted Fever Associated with Hypercytokinemia - Iwasaki, Hiromichi (American Society for Microbiology, 2001)
We report a patient with Japanese spotted fever caused by Rickettsia japonica who developed shock associated with hypercytokinemia. Elevated levels of cytokines (macrophage colony-stimulating factor, interleukin 1 beta, interleukin 10, and gamma interferon) decreased rapidly after a combination treatment using an antibiotic (minocycline hydrochloride [MINO]) and methylprednisolone; however, tumor necrosis factor alpha levels were increased. The patient's fever relapsed and was resolved only after the addition of ciprofloxacin hydrochloride. The administration of new quinolones alone may be another useful form of treatment to eradicate R. japonica even if the symptoms of hypercytokinemia appear to improve with the administration of MINO and methylprednisolone.